Snitches Get Stitches and End Up in Ditches: A Systematic Review of the Factors Associated With Whistleblowing Intentions - Nicholls, Adam R.; Fairs, Lucas R. W.; Toner, John; Jones, Luke; Mantis, Constantine; Barkoukis, Vassilis; Perry, John L.; Micle, Andrei V.; Theodorou, Nikolaos C.; Shakhverdieva, Sabina; Stoicescu, Marius; Vesic, Milica V.; et al. (Frontiers in Psychology, 2021)
Blowing the whistle on corruption or wrongdoing can facilitate the detection, investigation, and then prosecution of a violation that may have otherwise gone undetected. The purpose of this systematic review was to identify the factors that are associated with intentions to blow the whistle on wrongdoing. We searched Academic Search Premier, CINAHL Complete, Education Research Complete, ERIC, Medline, PsycARTICLES, PsycINFO, Regional Business News, and SPORTDiscus in January 2020. The quality of evidence was assessed using the Cochrane risk of bias tool. Of the 9,136 records identified, 217 studies were included in this systematic review. We identified 8 dimensions, 26 higher-order themes, and 119 lower-order themes. The whistleblowing dimensions were personal factors, organizational factors, cost and benefits, outcome expectancies, the offence, reporting, the wrongdoer, and social factors. Based on the findings, it is apparent that organizations should empower, educate, protect, support, and reward those who blow the whistle, in order to increase the likelihood on individuals blowing the whistle on corruption and wrongdoing. A combined approach may increase whistleblowing intentions, although research is required to test this assertion. From a policy perspective, more consistent protection is required across different countries.